2024
DOI: 10.1002/ieam.4906
|View full text |Cite
|
Sign up to set email alerts
|

Using emerging science to inform risk characterizations for wildlife within current regulatory frameworks

Mark S. Johnson,
Michael Beking,
Eric M. J. Verbruggen
et al.

Abstract: Many jurisdictions have regulatory frameworks that seek to reduce the effects of environmental exposures of anthropogenic chemicals on terrestrial wildlife (i.e., mammals, birds, reptiles, and amphibians). The frameworks apply for new and existing chemicals, including pesticides (prospective assessments), and to environmental contamination from releases (retrospective risk assessments). Relatively recently, there have been many scientific advances that could improve risk estimates for wildlife. Here, we briefl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 40 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…As reflected in summaries of the various regulatory regimes for wildlife risk assessment (Johnson et al, 2024), decision-makers (typically regulatory entities) require that risk assessments address clear hypotheses from which to make decisions. Guidance and methods specific to wildlife are needed to identify the discrete information that is expected and to describe how it will be evaluated.…”
Section: Risk Characterization In Wildlife Risk Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…As reflected in summaries of the various regulatory regimes for wildlife risk assessment (Johnson et al, 2024), decision-makers (typically regulatory entities) require that risk assessments address clear hypotheses from which to make decisions. Guidance and methods specific to wildlife are needed to identify the discrete information that is expected and to describe how it will be evaluated.…”
Section: Risk Characterization In Wildlife Risk Assessmentmentioning
confidence: 99%
“…As a result, guidance on ecological risk assessment, including for wildlife, is relatively standardized and has not been explicitly revised to reflect new approaches. However, the review of regulatory guidance on wildlife found that many jurisdictions have flexibility to include NAMs and other emerging science if it can apply in a weight of evidence approach to enhance and augment the characterization of risk (Johnson et al, 2024).…”
Section: Risk Characterization In Wildlife Risk Assessmentmentioning
confidence: 99%
See 2 more Smart Citations